Pharmaceutical Development and Evaluation of A Nutmeg-Loaded Topical Ointment for Analgesic and Anti-Inflammatory - Shaik Arifah naaz; Shaik Jahurunnisa; Perumalla Roshini; Mannava Bhavana; Asiya Begum; Nadendla Ramarao (The Bioscan, 2026)
Goal: To formulate and evaluate a topical ointment with nutmeg for analgesic and anti-inflammatory properties. Objectives: To Create a stable ointment with nutmeg extract, analyze its physicochemical characteristics, and test its effectiveness. Methodology: Nutmeg extract from Myristica frangrans was added to an ointment base and assessed for appearance, pH, Spreadability, viscosity, drug content, and in-vitro release, analgesic and anti-inflammatory properties were evaluated and contrasted with a commercial reference. Discussion: The formulation shows good physicochemical properties, and a notable decrease in pain and inflammation. In conclusion, nutmeg-loaded ointment showed good stability and release properties along with promising topical analgesic and anti-inflammatory effects.